2006
DOI: 10.1016/j.molcel.2005.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Nup-PI: The Nucleopore-Promoter Interaction of Genes in Yeast

Abstract: Our previous work identified the inner basket of the NPC as a physical activation/protection station for force-tethered, epigenetically silenced genes. Here we show that a specific nucleopore-to-gene-promoter interaction (Nup-PI) is an early physiological event of gene activation. Nup-PI was discovered with chromatin endogenous cleavage (ChEC) experiments that mapped in vivo the genomic interaction sites of the nucleoporin Nup2p fused to microccocal nuclease (Nup2-MN). Strong Nup-PI, cleavage by Nup2-MN, is ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
235
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(248 citation statements)
references
References 26 publications
11
235
2
Order By: Relevance
“…Examples of this in yeast are the preference of telomeres (Hediger et al 2002), centromeres (Heun et al 2001a), and silenced chromatin (Maillet et al 1996;Feuerbach et al 2002) for the nuclear periphery, the localization of various highly expressed and inducible genes to nuclear pores (Brickner and Walter 2004;Casolari et al 2004Casolari et al , 2005Schmid et al 2006), and the colocalization of ribosomal DNA and a majority of tRNA genes at the nucleolus. To accommodate each of these known levels of organization, there are likely to be multiple collaborating mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of this in yeast are the preference of telomeres (Hediger et al 2002), centromeres (Heun et al 2001a), and silenced chromatin (Maillet et al 1996;Feuerbach et al 2002) for the nuclear periphery, the localization of various highly expressed and inducible genes to nuclear pores (Brickner and Walter 2004;Casolari et al 2004Casolari et al , 2005Schmid et al 2006), and the colocalization of ribosomal DNA and a majority of tRNA genes at the nucleolus. To accommodate each of these known levels of organization, there are likely to be multiple collaborating mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The long-range movement of at least one inducible gene requires actin/myosin (Chuang et al 2006). The transcription-dependent tethering of some genes at the nuclear pore depends on interactions between the gene promoters and the basket of the nuclear pore complex (Schmid et al 2006). Centromere clustering at the spindle pole body requires microtubules (Bystricky et al 2004), as does homologous recombination, which requires spatial proximity of the two loci (Thrower et al 2003).…”
mentioning
confidence: 99%
“…It has been suggested that chromatin loops are formed through association of insulator elements with the nuclear pores (32,33,52). It is therefore possible that the barrier elements flanking HMR (21,22) or the hypersensitive sites at this locus (45) associate with nuclear pores or active chromatin hubs and cluster in the nucleus, the consequence of which would be to align HMR-E and HMR-I in close proximity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in yeast the promoters and terminators of genes are in close proximity to one another (3,48) and tethered to the nuclear pore (10,52). The consequence of this spatial organization is that the DNA between these regulatory elements is looped out.…”
mentioning
confidence: 99%
“…These transcribed genes interact with components of the nuclear pore complex (NPC) 4 (5,(7)(8)(9)(10), perhaps facilitating efficient mRNA processing and export. Although this phenomenon of locus association with the nuclear periphery has been reproducibly observed in yeast (5)(6)(7)(8)(9)(10), critical questions remain unanswered regarding the mechanism of locus recruitment to the NPC. Transcription factors, chromatin modifying complexes, and the transcription machinery itself have each been independently implicated in directing active loci to the NPC (8 -12), perhaps suggesting a recruitment mechanism dependent upon transcription initiation.…”
mentioning
confidence: 99%